Adhesive systems used in the European particleboard, MDF and OSB industries*. Issue 2 (15th March 2018) - Mantanis, George I.; Athanassiadou, Eleftheria Th.; Barbu, Marius C.; Wijnendaele, Kris
ABSTRACT: In this work, the adhesive systems used today in the European industries of particleboard, medium density fibreboard (MDF) and oriented strand board (OSB) are discussed. The structure of particleboard, MDF and OSB markets in Europe in relation to the types of adhesives and product specifications are presented as well. It is noticeable that new markets for wood-based panels like particleboard and fibreboard, known as non-furniture markets, are growing in Europe at a fast rate. It was concluded that most of the technological changes concerning the adhesive systems applied and additives have been realised from the need for niche panel products, the obligation to reach even lower formaldehyde emissions, and the necessity to decrease production costs due to the stringent competition in the market of wood-based panels.